Hybrid procedure combining endoscopic gallbladder lavage and internal drainage with elective cholecystectomy for acute cholecystitis: A prospective pilot study (The BLADE study). Issue 4 (26th February 2018) - Doi, Shinpei; Yasuda, Ichiro; Mabuchi, Masatoshi; Iwata, Keisuke; Ando, Nobuhiro; Iwashita, Takuji; Uemura, Shinya; Okuno, Mitsuru; Mukai, Tsuyoshi; Adachi, Seiji; Taniguchi, Keizo
Abstract : Background and Aim: Percutaneous transhepatic drainage is the most common method for non‐operative gallbladder drainage, but the technique does have several disadvantages because of its invasive nature and requirement for continuous drainage. To overcome these disadvantages, we developed a novel procedure, endoscopic gallbladder lavage followed by stent placement, carried out in a single endoscopic session. Our aim was to prospectively evaluate the efficacy and safety of this procedure in patients with acute cholecystitis. Methods: Patients diagnosed with moderate cholecystitis at four tertiary care centers were enrolled in this study. We initially placed a 5‐Fr tube to carry out gallbladder lavage. The tube was then cut to the optimal length and placed as a stent. Main outcomes were procedural and clinical success rates. Results: The procedure was attempted in 40 patients and was successful in 30 (75.0%). Minor adverse events occurred in two (5.0%) patients: perforation of the cystic duct by the guidewire in one patient and pancreatitis in the other. Among the 30 patients in whom the procedure was successfully done, clinical resolution was obtained in 29 (96.6%). Elective cholecystectomy was carried out in 37 patients (92.5%), with a median delay after drainage of 42 days (range, 12–138 days). There were no adverse events during the waiting period. Conclusions: Gallbladder rinsing followed by internal drainage using a 5‐Fr nasobiliary tube is considered an effective and safe alternative to other techniques, providing an acceptable success rate in patients with acute cholecystitis prior to elective surgery. Clinical trial information: http://www.umin.ac.jp/ctr/index.htm (ID: UMIN‐000009680).